The Role of the Diocesan Synod in the Synodal Church - Patejuk, Krzysztof (Prawo Kanoniczne, 2023)
In the article titled "The Role of the Diocesan Synod in the Synodal Church," the author presents post-conciliar Church legislation relating to the institution of the diocesan synod. The article, based on ecclesial, theological and canon Law sources, presents the development of the synod over the years, and attempts to indicate its role in the synodal Church, which, according to Pope Francis, is "what God expects from the Church of the third millennium," through a comparative analysis with the reformed institution of the synod of bishops.